A Practical Approach for Identification of Magnetic Fabric Carriers in Rocks. Issue 5 (11th May 2021) - Elhanati, D.; Issachar, R.; Levi, T.; Weinberger, R.
Abstract: Magnetic fabric analyses of rocks by anisotropy of magnetic susceptibility (AMS) are a robust petrofabric tool that has been used in varied geological environments and tectonic settings. A fundamental difficulty of this method is to define the dominant magnetic phases and their resulting geological interpretation. We study the magnetic behavior of rocks by simulating data of mixed magnetic phases (i.e., diamagnetic, paramagnetic, and ferromagnetic). We show that it is possible to recognize the dominant magnetic phases by measuring the mean susceptibility at room temperature ( k m RT ) and at low temperature ( k m LT ). Distinct regions of magnetic phase dominancy are demonstrated in k m LT / k m RT versus k m RT and k m LT versus k m RT plots. We present a comprehensive approach by coupling the magnetic phase dominancy with possible magnetic fabrics, which are obtained from AMS measured at room and low temperatures (RT‐AMS and LT‐AMS) and anisotropy of anhysteretic remanent magnetization, into a scenario table. Application of this table allows a robust procedure for determining which magnetic phases are dominant, and permits a fast and reliable geological interpretation in complex settings. Key Points: We present a robust procedure for determining the anisotropy of magnetic susceptibility (AMS) carriers (ferro, para, and diamagnetic phases) Mean susceptibility at room and low temperatures defines the respective contributions of the magnetic phases to the rock's susceptibility A novel scenario table, coupling respective contributions and associated magnetic fabrics, allows reliable interpretation of AMS data